Nothing : A Very Short Introduction - Close, Frank (Oxford, New York Oxford University Press, 2009)
What is 'nothing'? What remains when you take all the matter away? Can empty space - a void - exist? This Very Short Introduction explores the science and history of the elusive void: from Aristotle's theories to black holes and quantum particles, and why the latest discoveries about the vacuum tell us extraordinary things about the cosmos.
Include Illustration and Index
Keywords: Nothing (Philosophy) -- Physics--Philosophy -- Cosmology